Analisis Efektivitas Pertukaran Informasi Otomatis Dalam Menangkal Penghindaran Pajak Pada Direktorat Jenderal Pajak Tahun 2018-2019 - Putri Ayu Lestari; Chairil Anwar Pohan (Jurnal Ilmu Administrasi Publik, 2021)
Effective so far. This can be seen in the Automatic Exchange of Information (AEoI), where important data has been exchanged through the Common Transmission System  (CTS).  However, the  Indonesian Directorate General of Taxes still faces obstacles in this regard, for example the different readiness and capacity of the internal system for automatic information exchange in each country. Different completeness of data from partner countries can affect the quality of data information. The author suggests that the readiness of the internal system regarding the completeness of data from partner countries be further improved and resolved multilaterally. Security and confidentiality of domestic and international taxpayer account data must also be a priority and strictly guarded.